Gene Expression Patterns Associated with Peroxisome Proliferator-activated Receptor (PPAR) Signaling in the Longissimus dorsi of Hanwoo (Korean Cattle) - Lim, Dajeong; Chai, Han-Ha; Lee, Seung-Hwan; Cho, Yong-Min; Choi, Jung-Woo; Kim, Nam-Kuk (Animal bioscience, 2015)
Adipose tissue deposited within muscle fibers, known as intramuscular fat (IMF or marbling), is a major determinant of meat quality and thereby affects its economic value. The biological mechanisms that determine IMF content are therefore of interest. In this study, 48 genes involved in the bovine peroxisome proliferator-activated receptor signaling pathway, which is involved in lipid metabolism, were investigated to identify candidate genes associated with IMF in the longissimus dorsi of Hanwoo (Korean cattle). Ten genes, retinoid X receptor alpha, peroxisome proliferator-activated receptor gamma (PPARG), phospholipid transfer protein, stearoyl-CoA desaturase, nuclear receptor subfamily 1 group H member 3, fatty acid binding protein 3 (FABP3), carnitine palmitoyltransferase II, acyl-Coenzyme A dehydrogenase long chain (ACADL), acyl-Coenzyme A oxidase 2 branched chain, and fatty acid binding protein 4, showed significant effects with regard to IMF and were differentially expressed between the low- and high-marbled groups (p<0.05). Analysis of the gene co-expression network based on Pearson's correlation coefficients identified 10 up-regulated genes in the high-marbled group that formed a major cluster. Among these genes, the PPARG-FABP4 gene pair exhibited the strongest correlation in the network. Glycerol kinase was found to play a role in mediating activation of the differentially expressed genes. We categorized the 10 significantly differentially expressed genes into the corresponding downstream pathways and investigated the direct interactive relationships among these genes. We suggest that fatty acid oxidation is the major downstream pathway affecting IMF content. The PPARG/RXRA complex triggers activation of target genes involved in fatty acid oxidation resulting in increased triglyceride formation by ATP production. Our findings highlight candidate genes associated with the IMF content of the loin muscle of Korean cattle and provide insight into the biological mechanisms that determine adipose deposition within muscle.